Correlation of placental morphometry with the birth weight of newborn in Kerala population - Rajeev, Akshara Venmalassery; Goothy, SaiSailesh Kumar; Srinivasan, Chitra (Journal of Bangladesh Society of Physiologist, 2020)
Background:Morphology and morphometric measurements of the placenta will provide an insight into the aetiology of newborn and maternal complications. Objective:This study aimed to observe the gross morphometric assessment of placenta and to correlate the placental indices with birth weight of the baby in hypertensive and normal pregnancies. Methods:The present study was a comparative descriptive study with analytical components. A total of 86 pregnant women comprising 40 normotensive subjects and 46 hypertensive women within the age group of 18-40 years, parity between 1-4, gestational age between 37 weeks-40 weeks, who attended antenatal clinic of the hospital and delivered by either vaginal route or caesarean section were included in this study. After collecting their placenta, the weight, diameter, surface area, thickness, shape of the placentae was recorded. Weight and sex of baby was also recorded. For statistical analysis, Pearson correlation coefficient test was employed. Results: Positive correlation was observed between the placental surface area (p<0.05; p<0.001), diameter (p<0.05; p<0.001) weight (p<0.001; p<0.05) and the corresponding birth weight of the baby among both the normotensive and the hypertensive mothers. All these relationships were statistically significant. Conclusion: From this study, it can be concluded that placental morphometry has a direct relationship with the birth weight of the baby irrespective of the blood pressure of the mother during pregnancy.The study results may help in understanding of the maternal-placental programming of chronic diseases J Bangladesh Soc Physiol. 2020, December; 15(2): 91-97